Barcode Attendance System Based On Visual Basic 6.0 At PT. Priority - Mujiyono Mujiyono; Budi Hartono; Dendy Kurniawan (Lembaga Pengembangan Kinerja Dosen, 2022)
The attendance system aims to make it easier for employees to attend the office and this system uses Visual Basic software. The problem with why you have to use this system is because employee attendance still uses manual methods so it cannot be effective and efficient at work. The advantage that can be obtained by using this system is that it can make it easier for employees to be absent from the office by using computer facilities using barcodes. The benefits provided to the company are to simplify and speed up the work of employees so that they can increase employee discipline at the PT company. Priority